Interprofessional communication as an important tool of the work process in Primary Health Care (Research, Society and Development, 2021)
Communication is a strategic element for the realization of Health Care carried out by interdisciplinary teams. Scientific evidence reveals that the communicative process is determined by factors of different nature, raising the hypothesis of a different perception of it by different professional categories. The study aimed to investigate the intervening factors in the perception of Primary Health Care professionals about interprofessional communication. This is a cross-sectional descriptive study with a quantitative approach. A structured online questionnaire was adopted, conveyed through the Google Forms® platform. The sample consisted of 58 health professionals distributed among 8 categories. The results revealed that interprofessional communication is perceived as more intense between Community Health Agents and other professional categories. Those categories that are not part of the basic team are less remembered in the communicative process and managers have a percentage of 50% recognition among the categories that act as speakers. Organizational and structural issues were identified as aspects that produce failures in the team's communication. Therefore, the positive perception of communication with the Community Health Agents and managers is concluded due to the respective roles of mediators and planners of the health actions they occupy and, due to the strategic and determining role that communication plays in the quality of the service provided, more attention to the communicative process by researchers and managers is necessary to overcome factors that still interfere negatively in it and, consequently, in the quality of Health Care offered to the assisted community.